Pengembangan Dashboard Responsif Web pada Proses Bisnis Bank Air Kami Dengan Laravel Filament - Ramadhan, Daud Hidayat; Sujarwo, Ari (CV. Green Publisher Indonesia, 2025)
This research designed and implemented a responsive web dashboard for Bank Air Kami to support transparent, adaptive, and data-driven business governance. Our Water Bank is currently a producer of bottled drinking water and has the potential to develop itself into a water filter brand and management services, so reliable information control tools are needed. The system integrates the Internet of Things (IoT) for water quality sensor data acquisition, GIS visualization for spatial contexts, as well as Role-Based Access Control (RBAC) through the Laravel Filament framework for security and role management. The results of the evaluation show that the dashboard improves near-real-time monitoring of water conditions, facilitates historical audits, and provides relevant performance indicators for operational and strategic decision-making. The main contribution of this research is to present a monitoring solution that is not only technical, but also the foundation of business governance in the development of the water service ecosystem.